2010
DOI: 10.1002/ptr.2970
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C increases the fecal fat excretion by chitosan in guinea‐pigs, thereby reducing body weight gain

Abstract: The aims of this study were to investigate the antiobesity properties of chitosan on its own, as well as in the presence of vitamin C, in vivo. Hartley guinea-pigs were divided into Control (normal diet), F-control (high fat diet), Chitosan (high fat diet with 5.0% chitosan) and Chito-vit C (high fat diet with 5.0% chitosan containing 0.5% vitamin C) groups, respectively. The effects of chitosan, both alone and in the presence of vitamin C, on body weight, total fecal weight, fecal composition and plasma lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…A mild ascending trend in fecal fat excretion was noted among the three high fat groups on the order of HF (159.5 mg/day) < HF1X (165.0 mg/day) < HF2X (174.5 mg/day). As previously reported by Jun et al [ 19 ], there was a positive relationship between reduced dietary fat absorption and elevated fecal fat output.…”
Section: Resultssupporting
confidence: 80%
“…A mild ascending trend in fecal fat excretion was noted among the three high fat groups on the order of HF (159.5 mg/day) < HF1X (165.0 mg/day) < HF2X (174.5 mg/day). As previously reported by Jun et al [ 19 ], there was a positive relationship between reduced dietary fat absorption and elevated fecal fat output.…”
Section: Resultssupporting
confidence: 80%
“…Among the four HF groups, a markedly higher (p < .05) fecal fat excretion (about 1.1-fold) was observed in the BC198S38 group (50.6 mg/g). As previously reported by Jun et al (2010), a higher fecal fat output was basically associated with a lesser extent of dietary fat absorption. These results demonstrated that the feeding of multi-strain mixture would lead to a higher fecal fat output in this study.…”
Section: Assessments On Fecal Moisture Weight Fat and Scfassupporting
confidence: 82%
“…Accumulating literature also link vitamin D studies with bones while comparing BMI and general weight gains [ 14 16 ]. On the other hand, vitamin C however, has completely different functions in an in vitro experiments and in humans [ 20 22 ]; some previous studies show that, the metabolism of glucose in the insulin resistant people was improved, and the blood pressure was lowered in patients who took vitamin C supplementation [ 23 ]. Furthermore, vitamin C and vitamin E supplementation are shown to prevent molecular regulators that trigger the sensitivity of insulin as well antioxidant defense mechanisms through physical activities [ 24 ].…”
Section: Introductionmentioning
confidence: 99%